Two Refractory Immune Thrombocytopenia Case Reports Showing Responsiveness to Fostamatinib - Innao, Vanessa; Calogero, Rosalba Donatella; Lo Presti, Fabrizio; Consoli, Ugo (Case Reports in Hematology, 2023)
Immune thrombocytopenia (ITP) is immune-mediated platelet loss due to increased destruction and insufficient production. Treatment guidelines provide for first-line steroid-based therapies followed by thrombopoietin receptor agonists (TPO-RAs) and fostamatinib for chronic ITP. Fostamatinib demonstrated efficacy in phase 3 FIT trials (FIT1 and FIT2) mainly in second-line therapy resulting in the maintenance of stable platelet values. Here, we describe two patients with extremely heterogeneous characteristics that responded to fostamatinib after two and nine previous treatments. Responses were complete with stable platelet counts ≥50,000/μL and without any grade ≥3 adverse reactions. As in the FIT clinical trials, we confirm better responses to fostamatinib when used in the second or third line. However, its use should not be excluded in patients with longer and more complicated drug histories. Given the different mechanism of action of fostamatinib compared to TPO-RAs, it would be interesting to identify predictive factors of responsiveness applicable to all patients.